Changes in climate extreme indices and agricultural drought monitoring in the semi-arid areas of Borana zone, southern Ethiopia - Girma Asefa Bogale; Asfaw Kebede Kassa; Mengistu Mengesha Maja (Heliyon)
Climate variability and extremes negatively impact on agricultural productivity and production in arid and semi-arid areas of Ethiopia. This study evaluated changes in climate extreme indices in the semi-arid areas of Borana Zone. Data of daily rainfall, maximum and minimum temperature from 1993 to 2022 were acquired from the National Meteorological Institute of Ethiopia and Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS). R-package for climate extreme indices (RClimDex), Xlstat 2019, OriginPro, and ArcGIS software were used as data analysis tools to determine climate extreme indices, trends, and drought anomalies in the study area. Spatial and temporal variations in rainfall, temperature, and vegetation indices in the semi-arid Borana zone were analyzed using Google Earth Engine (GEE). The results revealed a decrease in the frequency of consecutive wet days (CWD), maximum 1-day precipitation amount (Rx1days), maximum 5-day precipitation amount (Rx5days), and very wet days (R95p) in Dire, Guchi, Wachele, and Moyale districts of Borana zone. Annual and monthly total precipitation (PRCPTOT) also decreased in Dhaso, Dilo, Dubluk, Guchi, Moyale, and Tatlate districts of the semi-arid areas of the zone over the study years. Warm spell duration index (WSDI), monthly or annual maximum of daily minimum temperature (TNx), warm nights (TN90p), and warm days (TX90p) showed an increase in the study area. However, standardized precipitation indices of R10, R20, R95p, and R99p indicated moderate drought across the studied districts of Borana zone. The Vegetation Condition Index (VCI) showed higher drought severity and spatial distribution in Dilo and Yabelo, whereas Temperature Condition Index (TCI) detected in Dire, Dubluk and Yabelo areas indicated drought stress due to moisture and thermal stress. Moisture-stress and thermal-stress play role in drought formation, whereas, drought severity is determined by moisture availability, which is dependent on rainfall. We demonstrate that the study area experienced moderate to severe drought frequent over the study years, and multiple satellite-based drought indices are necessary for better early warning and assessment of agricultural drought in the study area. Further studies that consider socioeconomic aspects of the farmers in the area are necessary to better understand the impacts of climate extremes on smallholder farmers, and devise location-specific adaptation strategies.